Improvement of Student Ecoliteracy through Contextual Teaching and Learning Based on Outdoor Study in Elementary Social Studies Learning - Nurbaeti, Iyus; Supriatna, Nana; Zulfikar, Hari Ahmad (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2020)
Ecoliteracy or Ecological Intelligence is intelligence that is built by understanding, awareness and life skills in harmony with the preservation of nature. This study began with an objective observation in the Binekas Elementary School in Bandung regarding the behavior of students related to environmental awareness. The observation of the behavior of class III students totaling 22 people showed that they were not accustomed to separating organic and inorganic waste, as well as damaging and picking vines in the school. This study aims to increase students' ecoliteracy through contextual teaching learning (CTL) based on outdoor study in elementary social studies learning. The teaching and learning process uses CTL with the material 'Protecting the Environment for the Preservation of Plants and Animals